Virtual Teams: A Smart Literature Review of Four Decades of Research - Kimura, Takuma (Human Behavior and Emerging Technologies, 2024)
The increasing utilization of virtual teams—driven by advancements in information and communication technology and the forces of globalization—has spurred significant growth in both theoretical and empirical research. Based on the smart literature review framework, this study harnesses artificial intelligence techniques, specifically natural language processing and topic modeling, to extensively analyze the trends in virtual team research spanning the last four decades. Analyses of a dataset comprising 2,184 articles from Scopus-indexed journals discern 16 distinct topics, encompassing critical areas such as communication, leadership, and trust. The trajectory of research topics in this field has witnessed increasing diversification over time. Key subjects such as learning, communication, trust, and leadership have consistently maintained their presence among the ten most frequently explored topics. In contrast, emerging areas such as agile development and patient care have recently become some of the most prominent themes. Employing the state-of-the-art topic modeling technique, BERTopic, this study furnishes a comprehensive and dynamic panorama of the evolving landscape within virtual team research.